Environmental heritage and cultural diversity: milestones in the struggle for indigenous peoples' rights in Brazil (2011-2014) - Martinez, Paulo Henrique [UNESP] (Fundacao Getulio Vargas-fgv, 2023)
Examination of environmental heritage, cultural diversity, and educational action in museums in the political mobilization of indigenous populations for constitutional rights and public policies, between 2011 and 2014. The sources are the daily press and institutional, public, and private documents. The study identified new impulses in the struggles for indigenous peoples' rights in South America. In Brazil, the proposed Constitutional Amendment No. 215, the National Policy for Environmental and Territorial Management of Indigenous Lands and the reform of the Forest Code have catalyzed national and regional disputes. Heritage, culture, and museums become vectors in the construction of intercultural and indigenist education.
Keywords: Environmental history; heritage; Indigenous populations